Association between KCNQ1 genetic variants and QT interval in a Chinese population. Issue 10 (21st June 2013) - Yu, W.; Zhang, F.; Hu, W.; Zhang, R.; Wang, C.; Lu, J.; Jiang, F.; Tang, S.; Peng, D.; Chen, M.; Bao, Y.; Xiang, K.; et al.
Abstract Aim There is a close link between electrocardiographic ventricular repolarization QT parameters and Type 2 diabetes. The aim of the present study was to assess the effects of QT‐related and diabetes‐related variants in KCNQ1 on QT interval in a Chinese population. Methods We recruited 2415 patients with Type 2 diabetes and 1163 subjects with normal glucose regulation in the present study. QT interval was obtained and the heart rate‐corrected QT interval (QTc) was calculated using Bazett's formula. Four single nucleotide polymorphisms in KCNQ1 were selected (rs12296050, rs12576239, rs2237892 and rs2237895) and genotyped. Results In participants with normal glucose regulation, the minor allele T of rs12296050 was associated with a 3.46‐ms QTc prolongation under an additive model (P = 0.0109, empirical P = 0.0498). In patients with Type 2 diabetes, we did not find any association for the single nucleotide polymorphisms. Conclusions Our findings indicate that KCNQ1 is associated with QT interval in a Chinese population with normal glucose regulation.